Isolation of MDCK cells with low expression of mdr1 gene and their use in membrane permeability screening - BOKULIĆ ANA; PADOVAN JASNA; STUPIN-POLANČEC DARIJA; MILIĆ ASTRID (Acta Pharmaceutica)
The Madin-Darby canine kidney (MDCK) cell line is frequently used for permeability screening in drug discovery. It contains endogenous transporters, most prominently canine multidrug resistance P-glycoprotein (Mdr1), which can interfere with studies of P-glycoprotein substrate assessment and permeability measurements. Because MDCK wild type (WT) is genetically heterogeneous, an isolation procedure was investigated in this study to obtain the subclonal line with low P-glycoprotein expression. The best clone obtained had up to 3-fold lower amprenavir efflux and P-glycoprotein expression in comparison to WT. Of 12 standard compounds tested that exhibited active efflux in WT cells, 11 showed a decrease in efflux in the isolated clone. However, the decrease was not below the cut-off value of 2, indicating residual P--glycoprotein activity. Clone isolation via the limiting dilution method, combined with bidirectional amprenavir permeability for clone selection, successfully identified MDCK clones with substantially lower P-glycoprotein efflux and has been demonstrated as a useful tool for assessing passive permeability in early drug discovery.